K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

1 tháng 8 2016

đề bài có đúng k z bạn

25 tháng 9 2015

96-3.(x+a)=42

     3(x+a)=96-42

     3(x+a)=54

         x+a=54:3

         x+a=18

 

26 tháng 9 2018

(3x - 6) + 9 = 34 . 3

(3x - 6) + 9 = 35

(3x - 6) + 9 = 243

3x - 6 = 243 - 9

3x - 6 = 234

3x = 234 + 6

3x = 240

x = 240 : 3

x = 80

Vậy x = 80.

96 + 3 . (x - 1) = 42

3 . (x - 1) = 42 - 96

3 . (x - 1) = -54

x - 1 = -54 : 3

x - 1 = -18

x = -18 + 1

x = -17

Vậy x = -17

a,x=80

~~~~~~~~~~~~
~~~~~~~~~~~
~~~~~~~~~~~~~~

23 tháng 7 2019

a) 3.x+7=25

   3.x     = 25 -7

.  3.x     = 18

      x.    = 18 :3

.     x.    6

23 tháng 7 2019

 a. 3.x+7=25

<=> 3x = 18

<=> x = 6

b. (5.x+4)-1=23

<=> 5x + 4 = 24

<=> 5x = 20

<=> x = 4

c. 96-3(x+1)=42

<=> 3(x + 1) = 54

<=> x + 1 = 18

<=> x = 17

d. 2x=16

<=> 2x = 24

<=> x = 4

e. x2=16

<=> \(\orbr{\begin{cases}x^2=4^2\\x^2=\left(-4\right)^2\end{cases}}\)

<=> x = \(\pm\)4

20 tháng 2 2020

a) ( 3x-17) . 45= 46

( 3x -17) = 46: 45

( 3x-17) = 4

3x = 4+17

3x= 21

x= 21:3

x=7

Vậy....

20 tháng 2 2020

b) 3 |x-5|-23=(-2)3

3 |x-5| -23 = -8

3 |x-5| = -8+23

3 |x-5| = 15

| x -5| = 15:3

|x-5| = 5

TH1: x- 5= 5

x= 5+5

x= 10

TH2: x -5 = -5

x= -5+5

x= 0

Vậy...

`#3107.101107`

`a)`

`4,57 \times 42 + 5,43 \times 42`

`= 42 \times (4,57 + 5,43)`

`= 42 \times 10`

`= 420`

`b)`

`8,4 \times 96 + 1,6 \times 96`

`= 96 \times (8,4 + 1,6)`

`= 96 \times 10`

`= 960`

8 tháng 11 2023

a) 4,57x42+5,43x42
= (4,57+5,43)x42
= 10x42
=420

b) 8,4x96+1,6x96
= (8,4+1,6)x96
= 10x96
= 960

 

 

 

11 tháng 7 2023

\(96-3\left(x+1\right)=42\)

\(=>3\left(x+1\right)=96-42\)

\(=>3\left(x+1\right)=54\)

\(=>x+1=54:3\)

\(=>x+1=18\)

\(=>x=18-1\)

\(=>x=17\)

11 tháng 7 2023

\(96-3\left(x+1\right)=42\)

\(\Rightarrow3\left(x+1\right)=96-42\)

\(\Rightarrow3\left(x+1\right)=54\)

\(\Rightarrow x+1=54:3\)

\(\Rightarrow x+1=18\)

\(\Rightarrow x=18-1\)

\(\Rightarrow x=17\)

6 tháng 12 2015

a. (-7)+14-(-7)+4.(-14)+12

= (-7)+14+7+(-56)+12

= (-7+7)+14-56+12

= 0 + 14+12-56

= -30

b. (3x-6).3=34

=> 3x-6=34:3

=> 3x-6=33

=> 3x-6=27

=> 3x=27+6

=> 3x=33

=> x=33:3

Vậy x=11.

c. 96-3(x+1)=42

=> 3(x+1)=96-42

=> 3(x+1)=54

=> x+1=54:3

=> x+1=18

=> x=18-1

Vậy x=17.

10 tháng 9 2015

96 - 3(x+1)= 42

3(x+1) = 96 - 42 = 54

x + 1 = 54 : 3 = 18

x = 18 - 1 = 17

2 tháng 8 2021

x=18-1=17

3 tháng 3 2018

c)96 - 3.(x + 1) = 42

3.(x + 1)= 96 - 42

3.(x + 1) = 54

x + 1= 54:3

x + 1= 18

x = 18 - 1

x = 17

25 tháng 6 2024